Faktor-Faktor yang Berhubungan dengan Kepuasan Konsumen Kopi Bubuk Cap Bintang Jaya Di Kabupaten Lampung Utara - Soraya, Lulu; Lestari, Sri Puji; Sari, Yuni Elmita; Putra, Ungki Prabowo; Bakti, Aji Setiya (AgriMalS, 2025)
study aims to to determine consumer satisfaction and analyze factors related to consumer satisfaction with Bintang Jaya Brand Ground Coffee in North Lampung Regency. Coffee is one of the leading commodities in this area, and Bintang Jaya Brand Ground Coffee faces tight competition in the local market due to price differences with competitors. This study was conducted with a quantitative approach using a survey method of 100 respondents selected by accidental sampling. Data were collected through questionnaires and analyzed using Spearman's Rank correlation with a 5% confidence level through SPSS version 26. Consumers are satisfied with Cap Bintang Jaya Ground Coffee. This satisfaction is shown by a positive perception of coffee quality. In addition, consumers are also satisfied with the simple design of the coffee packaging. Consumers are satisfied with the price set, because consumers already know about the quality provided by Cap Bintang Jaya Ground Coffee. Consumers are satisfied with the experience gained when buying and consuming Cap Bintang Jaya Ground Coffee. And Cap Bintang Jaya Ground Coffee is easy to find on the market, this also affects farmer satisfaction. 2. Based on the results of the Spearman rank correlation analysis, it can be seen that the factors that are positively correlated with consumer satisfaction are product quality and place/location.